2003
DOI: 10.1074/jbc.m300616200
|View full text |Cite
|
Sign up to set email alerts
|

Iron Regulatory Protein 2 as Iron Sensor

Abstract: Iron regulatory protein 2 coordinates cellular regulation of iron metabolism by binding to iron responsive elements in mRNA. The protein is synthesized constitutively but is rapidly degraded when iron stores are replete. This iron-dependent degradation requires the presence of a 73-residue degradation domain, but its functions have not yet been established. We now show that the domain can act as an iron sensor, mediating its own covalent modification. The domain forms an ironbinding site with three cysteine re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 26 publications
(16 reference statements)
2
33
0
Order By: Relevance
“…Our results indicate that specific structural motifs are important for controlling protein oxidation. It is noteworthy that similar observations have recently been reported for iron regulatory protein 2, which coordinates cellular regulation of iron metabolism by binding to iron responsive elements in mRNA (27). Oxidative modifications of proteins may thus be site-specific and require a specific juxtaposition of reactive moieties rather than being driven simply by the chemical reactivity of amino acid side chains.…”
Section: Discussionsupporting
confidence: 70%
“…Our results indicate that specific structural motifs are important for controlling protein oxidation. It is noteworthy that similar observations have recently been reported for iron regulatory protein 2, which coordinates cellular regulation of iron metabolism by binding to iron responsive elements in mRNA (27). Oxidative modifications of proteins may thus be site-specific and require a specific juxtaposition of reactive moieties rather than being driven simply by the chemical reactivity of amino acid side chains.…”
Section: Discussionsupporting
confidence: 70%
“…Although calcein fluorescence did not indicate an increase in the labile iron pool, possibly this method was not sufficiently sensitive to measure an increase in intracellular iron from the sham air. Alternatively, IRP2 degradation requires oxygen (27). Recently, Leibold and colleagues demonstrated that oxygen status plays a central role in IRP2 stability (23,46).…”
Section: Discussionmentioning
confidence: 99%
“…Alkylation and Lys-C digestion of actin and pY-actin were performed as described (34). The parent molecules and digests were analyzed by reverse-phase chromatography on a narrow-bore C 18 column (Vydac, Hesperia, CA) and by mass spectrometric analysis as described (35), except that the instrument was an Agilent Technologies (Palo Alto, CA) model 1100 HPLC coupled to an Agilent Technologies model G1969A mass spectrometer with a time-of-flight detector.…”
Section: Methodsmentioning
confidence: 99%